Revisiting the socioeconomic determinants of exclusive breastfeeding practices: evidence from Eastern Indonesia. (3rd July 2018) - Lo Bue, Maria C.; Priebe, Jan
Abstract: This paper attempts to fill several important research gaps on the socioeconomic determinants of exclusive breastfeeding practices. In contrast to previous studies that have focused on the timely initiation and duration of breastfeeding, this article examines exclusive breastfeeding practices. Using data on 1138 children from the Indonesian Family Life Survey East 2012, we revisited to what extent mothers' education levels and work in non-traditional sectors influence exclusive breastfeeding patterns. Furthermore, we investigated to what extent health-care demand and supply factors influence exclusive breastfeeding practices. Controlling for a wide range of individual, household, and community characteristics, our findings suggest that exclusive breastfeeding practices are affected positively by mothers' education and negatively by mothers' labour market participation in non-traditional employment contracts. Moreover, our results indicate that a higher availability and quality of health-care supply does not necessarily lead to better exclusive breastfeeding practices. Only when health-care supply was matched with a significant demand for such services, did we observe a higher chance for optimal exclusive breastfeeding.